Application of Variable Bit Rate Video in IPTV on Demand Services - Chuanfei Luo; Weijia Shi; Qing Xiao (Dianxin kexue)
Based on the engineering model for VBR video traffic, the flow characteristics of VBR video based on user requested arriving time interval was analyzed. Studies show that in compatible with the existing IPTV terminal and platform system, even without the use of any video smoothing technology, self-average can be obtained 30%～50% statistical gain through using statistical random characteristics of large scale VBR video traffic in IPTV on demand business. The feasibility and effectiveness of VBR video“self-average”characteristics in the application of IPTV on demand services were verified.